Effect Of Organizational Culture And Empowerment On Organizational Commitment To Improve Employee Performance In Puskesmas Ngemplak 1 - Wulandari, Astrilia; Subiyanto, Didik; Herawati, Jajuk (LPPM Universitas Bina Bangsa, 2021)
This study examines the effect of Organizational Culture and Empowerment on Organizational Commitment to improve Employee Performance at Puskesmas Ngemplak 1. This research was conducted on all employees of Puskesmas Ngemplak 1, totalling 40 people. This research is quantitative. The sample of this study used a sampling technique with a questionnaire or questionnaire. The sample data collection was carried out by distributing questionnaires directly to each employee. The number of questionnaires distributed and processed was as many as 20 questionnaires. Data processing in this study uses multiple linear regression analysis techniques, assisted by the SPSS program version 20.0. The results of this study indicate that organisational culture has a positive and significant effect on organisational commitment. Organisational culture has a positive and significant impact on performance. The empowerment of members has a positive and significant impact on organisational commitment. Assignment of members has a positive and significant effect on performance, and organisational commitment also positively and significantly impacts performance. This proves that organisational culture and member empowerment on organisational commitment significantly affect the performance of the employees of Puskesmas Ngemplak 1